Comparative Analysis of Black-Scholes and Garch Model in Rupiah and American Dollar with Short Strangle Strategy from 2009 to 2018 - Hadiana, Riza; Hendrawan, Riko (Journal of Social Research, 2023)
Foreign exchange transaction remains the most liquid trade in the world (Settlements, 2019). This paper examined the exchange rate of the US Dollar against Indonesian Rupiah at which volatility recorded the highest average of 1.98% and the lowest of 1.98% between 2009 and 2018. It shows that the existence of uncertainty or risk for economic actors. According to economists, the thing to protect the value of assets is by using available derivative products, The Option. The first model used for forecasting and determining the Option values is the Black-Scholes Model that uses historical volatility and some GARCH model to determine volatility. In this study, the object of the exchange rate of the US Dollar with Rupiah was comparing to two models using the average mean square error, and see how small the error results obtained. The results of the comparison of those two models found that during a month, the Black Scholes model had smaller errors for call and put values with a percentage of profits using a short strangle strategy was 83.75%. In contrast, over 2 months, the GARCH model showed better for call and put values with a profit percentage was 71.62%. Finally, the Black-Scholes model got a way better for call and put supplies with a percentage of the profit of 72.04% within 3 months.